Schirmer’s Test I and Determination of Intraocular Pressure in Healthy Common Buzzards (Buteo buteo) - Yaygingul, Rahime; Bozkan, Zeynep; Bulut, Osman; Cakmakci, Eser; Belge, Ali (Acta Scientiae Veterinariae, 2019)
Background: The structure of the eye in wild birds is 45% larger than that in humans, which provides excellent visual capacity but also makes them vulnerable to eye trauma. Trauma, neoplasia, infectious diseases of the ocular surface, uveitis, glaucoma, and corneal diseases in wild birds, but mainly trauma, can cause a reduction in their tear production; therefore, determining the amount of tear production in the wild birds is very important. Studies have shown that the results of the Schirmer’s tear test (STT) and intraocular pressure (IOP) values differ among wild bird species, and that both anesthesia and sedation affects these parameters. The main objective of the present study was to determined IOP and STT I values in healthy common buzzards (Buteo buteo). Materials, Methods & Results: Thirty healthy common buzzards were selected for the study following clinical and ophthalmic examinations. Following physical and clinical examinations of all subjects, routine ophthalmologic examinations were conducted, including reflex examinations (pupillary, palpebral, menace, dazzle) and direct ophthalmoscopy for the eyelids, conjunctiva, cornea, iris, lens, and fundus. All examinations were conducted without anesthesia or sedation while the birds were in the dorsal recumbent position, and the results of STT I and IOP were recorded. Both tests were repeated for the right and left eyes. The mean ± SE STT I values for the right and left eyes were 12.63 ± 0.51 and 12.43 ± 0.54 mm/min, respectively. A comparison between STT I values of the right and left eyes revealed no statistically significant differences (P > 0.620). The means and ranges of the TonoVet® IOP results for the right and left eyes were 32.06 ± 1.58 and 32.60 ± 1.51 mmHg, respectively. There was no statistically significant difference between the results of the test on the two eyes (P > 0.05). Discussion: Tear production is either increased or decreased in wild birds as a result of several types of eye diseases or trauma (1, 6). The most common method by which to determine tear production is either STT I (3), which is conducted without topical anesthesia, or STT II, which is conducted with topical anesthesia. As in our study, previous studies have used STT I as their method by which to determine tear production of wild birds. In a study conducted on 20 common buzzards, STT I values were 12.47 ± 2.66 mm/min. In our study using 30 common buzzards, the STT I value was 12.63 ± 0.51 mm/min for the right eye and 12.43 ± 0.54 mm/min for the left eye. There was no statistically significant difference between the results of the tests on the two eyes. In previous study with 25 common buzzards, IOP measured rebound tonometry was 5-30 (35-60). In our study, rebound tonometry results for IOP of 30 common buzzards were 32.06 ± 1.58 mmHg (16-47) for the right eye and 32.60 ± 1.51 mmHg (17-50) for the left eye. There was no statistically significant difference in IOP values between right and left eyes. Given that there are few studies on tear production and IOP in common buzzard, we believe that the results of this study will provide valuable new information to the literature.